Waqf Manager (Nazir) Coaching and Competence in The Development of Productive Waqf - Wildan Munawar; R Ali Pangestu; Qomaruddin S (Universitas Djuanda, 2022)
The development of productive waqf cannot be separated from the competent role of nazir in managing waqf. One of the efforts to improve Nazir's competence is through coaching. This study aims to determine the effect of coaching on increasing nazir's competence to develop productive waqf in Bogor Regency. The research method uses quantitative research with data collection techniques to distribute questionnaires. Data collection was based on a purposive sampling technique for nazir who had received coaching from the Indonesian Waqf Board and the Ministry of Religion, Bogor Regency. The data analysis technique uses Partial Least Square with the help of the Smart PLS 3 application to verify and confirm the coaching that has been done. The results showed that coaching had a positive and significant effect on increasing nazir's competence in developing productive waqf. The increasing competence of Nazir in the development of productive waqf is not enough just to have knowledge and understanding of the science of fiqh alone but must be equipped with competence in business management and entrepreneurship. So that the carried out must be more on the management and development of business-oriented waqf assets.